Caracterização agronômica e cor instrumental de linhagens de alface (Lactuca sativa l.) em cultivo convencional - Brito, Beatriz Alvarenga de (Universidade Federal de São Carlos, 2026)
Lettuce (Lactuca sativa L.) is the most widely cultivated leafy vegetable in Brazil due to its broad adaptation to different edaphoclimatic conditions and its socioeconomic importance, especially for family farming. In response to the increasing demand for products with improved quality and extended postharvest shelf life, this study aimed to characterize and compare the agronomic performance and instrumental color of curly lettuce lines under field conditions. The experiment was conducted under field conditions using three commercial cultivars ('Vanda', 'Jade', and 'BS 155') and nine breeding lines developed by the GEHORT/UFSCar breeding program. The evaluated agronomic traits included shoot fresh weight (SFW), shoot dry weight (SDW), number of leaves (NL), maximum leaf width (MLW), maximum leaf length (MLL), stem diameter (SD), and stem length (SL). Instrumental color was assessed using the CIELAB color system, considering lightness (L*), chroma (C*), and hue angle (h°). Data were subjected to analysis of variance (ANOVA), and means were compared using the Scott-Knott test at the 5% significance level. A significant effect of genotype (p ≤ 0.05) was observed for all agronomic traits and colorimetric parameters evaluated. The results showed that some breeding lines exhibited superior agronomic performance compared with the commercial cultivars, whereas others showed similar performance, standing out for their greater biomass accumulation and more intense green coloration, characteristics desirable for lettuce commercial quality. Therefore, the best-performing breeding lines represent promising genetic material for lettuce breeding programs, contributing to the expansion of the genetic base of curly lettuce and the development of cultivars with high agronomic potential.
Agronomic characterization and instrumental color of Lettuce (Lactuca sativa L.) lines under conventional cultivation
Keywords: Hortaliça folhosa; Cultivares; Melhoramento genético; Alfacicultura; Leafy vegetable; Cultivars; Plant breeding; Lettuce cultivation; CIENCIAS AGRARIAS::AGRONOMIA; 2. Fome Zero e Agricultura Sustentável